2018
DOI: 10.1111/cxo.12550
|View full text |Cite
|
Sign up to set email alerts
|

Does Hofstetter's equation predict the real amplitude of accommodation in children?

Abstract: Purpose: The aim was to determine the distribution and associated factors of accommodative amplitude (AA) in six-to 12-year-old children and compare the results with those calculated using Hofstetter's formula. Methods: In a cross-sectional study in 2015, random sampling was done from urban and rural populations of Shahroud, northern Iran. Participating schoolchildren were examined for manifest, cycloplegic and subjective refraction, as well as uncorrected vision and visual acuity. The AA was measured with Don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
4
25
0
Order By: Relevance
“…Linear regressions for maximum and minimum mean AA fell in the middle of Hofstetter’s equation = 25 − (0.4 × age) for maximum AA and 15 − (0.25 × age) for minimum AA. Although the mean values of AA among various age groups in several studies were different from the predicted AA using Hofstetter’s equations [3335], the value of the overall mean AA in our findings was similar to the AA derived Hofstetter’s equations.…”
Section: Discussionsupporting
confidence: 60%
“…Linear regressions for maximum and minimum mean AA fell in the middle of Hofstetter’s equation = 25 − (0.4 × age) for maximum AA and 15 − (0.25 × age) for minimum AA. Although the mean values of AA among various age groups in several studies were different from the predicted AA using Hofstetter’s equations [3335], the value of the overall mean AA in our findings was similar to the AA derived Hofstetter’s equations.…”
Section: Discussionsupporting
confidence: 60%
“…According to the results, the emmetropic group showed the lowest AI prevalence at 3.74%, and the hyperopic group had the highest prevalence at 5.26%; however, this relationship was not statistically significant. It should be noted that some studies have reported lower AA in hyperopic compared to myopic and emmetropic individuals,33, 39, 40 which is in agreement with the results of the present study suggesting a higher AI prevalence in hyperopes. Regarding the reason for lower AA in hyperopic individuals, the theory proposed by McBrien and Millodot 40 can be mentioned.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the prevalence rates reported in these studies do not seem true and are believed to be mainly due to error in the diagnostic criterion. This issue is further confirmed in another study by Hashemi et al 33 …”
Section: Discussionsupporting
confidence: 79%
“…The formula is based upon analysis of historical data measured in subjects of all ages, including children, younger adults, pre-presbyopic adults, and presbyopic adults. A recent clinical study suggests that HF inaccurately predicts AC values in children, 35 which implies that Hofstetter should have excluded measurements taken in children when calculating the constants in his formula. We speculate that the formula might make more accurate predictions if different sets of constants are calculated for different age groups (young child, youth child, young adult, pre-presbyopic adult, and presbyopic adult).…”
Section: Discussionmentioning
confidence: 99%